Association between Abdominal Fat (DXA) and Its Subcomponents (CT Scan) before and after Weight Loss in Obese Postmenopausal Women: A MONET Study - Caroline Y. Doyon; Martin Brochu; Virginie Messier; Marie-Ève Lavoie; May Faraj; Éric Doucet; Rémi Rabasa-Lhoret; Isabelle J. Dionne (Journal of Obesity)
Introduction. Subcutaneous fat (ScF) and visceral fat (VF) measurements using CT scan are expensive and may imply significant radiation doses. Cross-sectional studies using CT scan showed that ScF and VF are significantly correlated with abdominal fat measured by DXA (AF-DXA). The association has not been studied after a weight loss. Objective. To determine (1) the associations between AF-DXA and ScF and VF before and after weight loss and (2) the associations between their changes. Methods. 137 overweight/obese postmenopausal women were divided in two groups (1-caloric restriction or 2-caloric restriction + resistance training). AF was assessed using DXA and CT scan. Results. Correlations between AF-DXA and ScF (before: r=0.87, after; r=0.87; P<.01) and, AF-DXA and VF (before: r=0.61, after; r=0.69; P<.01) are not different before and after the weight loss. Correlations between delta AF-DXA and delta ScF (r=0.72; P<.01) or delta VF (r=0.51; P<.01) were found. Conclusion. The use of AF-DXA as a surrogate for VF after weight loss is questionable, but may be interesting for ScF.